In vitro uptake studies of cell targeting agents and nanoparticles - Sasso, L. (2015)
Recent progress in synthetic chemistry has enabled the preparation of new highly-defined polymers that exhibit changes in their structure in response to environmental changes. These responsive nanomaterials may be desirable as carriers of drugs to deliver at the cellular and sub-cellular level. However, the endocytic pathways used by these nanoparticles to access cells must be defined. Carboxylated polystyrene beads (C-PB) of 50 and 100 nm size were chosen as ‘model’ nanomedicines and their route of uptake into cells characterised and compared to thermoresponsive PLGA-b-(PEGMA-co-PPGMA) and PLA-b-(DEGMA-co-OEGMA) block copolymers of 50-150 nm (‘candidate’ drug delivery systems) uptake. A number of protocols were optimised for endocytosis inhibition studies. Results reported that the inhibition of clathrin mediated endocytosis (CME) with chlorpromazine (CPZ) was cell- and time-dependent. After the maximal effect of the inhibitor, the endocytosis of human transferrin (Htf), a marker of CME, recovered up to uninhibited levels in 3T3 and HCT116 cells. Furthermore, high passage number and ageing of cells showed a resistance towards the inhibition of the uptake of Htf with CPZ. Both PLGA-b-(PEGMA-co-PPGMA) and PLA-co-(DEGMA-co-OEGMA) thermoresponsive block copolymers presented colloidal instability and aggregation that impeded further endocytic pathway internalization experiments. However, the results reported in this thesis question some of the interpretation in the literature of the susceptibility of cells to CPZ in the internalization of nanomaterials. New experimental settings for CPZ inhibition studies should be considered and protocols optimised in order to avoid incorrect and potentially misleading outcomes.